2009
DOI: 10.1007/s11814-009-0220-9
|View full text |Cite
|
Sign up to set email alerts
|

CFD simulation of gas-solid bubbling fluidized bed containing FCC particles

Abstract: The hydrodynamics of a bubbling gas-solid fluidized bed of 57.4 µm FCC particles was simulated by using a state-of-the-art two-fluid model integrating the kinetic theory of granular flow for particulate phase stresses. The overestimation of the bed expansion was resolved by using a suitable scale factor in the drag model as suggested by McKeen and Pugsley (T.R. McKeen, T.S. Pugsley, Powder Technol., 129, 139 (2003)). This study showed that the method was appropriate in simulation of a gas-solid fluidized bed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The TFM approach has been proofed and obtained great progress in modeling gas fluidization of Geldart B and D particles and dilute gas-solid flow. However, many researchers have found that the simulated bed expansion characteristics for dense bubbling beds or turbulent beds of Geldart A particles by the standard TFM approach are overestimated, which do not completely coincide with the experimental data (Ferschneider and Mege, 1996;Mckeen and Pugsley, 2003;Yang et al, 2003aYang et al, , 2003bZhang, 2004;Zimmermann and Taghipour, 2005;Cao, 2006;van Wachem and Sasic, 2008;Mao et al, 2008;Gao et al, 2008aGao et al, , 2008bHosseini et al, 2009;Li et al, 2009). The researchers argued that the fundamental cause resulting in the overestimated bed expansion is that the feature of aggregative fluidization caused by particle clustering is not considered in the current several universal drag laws, such as Gidaspow, Syamlal-O'Brien drag laws, etc.…”
Section: Article In Pressmentioning
confidence: 99%
“…The TFM approach has been proofed and obtained great progress in modeling gas fluidization of Geldart B and D particles and dilute gas-solid flow. However, many researchers have found that the simulated bed expansion characteristics for dense bubbling beds or turbulent beds of Geldart A particles by the standard TFM approach are overestimated, which do not completely coincide with the experimental data (Ferschneider and Mege, 1996;Mckeen and Pugsley, 2003;Yang et al, 2003aYang et al, , 2003bZhang, 2004;Zimmermann and Taghipour, 2005;Cao, 2006;van Wachem and Sasic, 2008;Mao et al, 2008;Gao et al, 2008aGao et al, , 2008bHosseini et al, 2009;Li et al, 2009). The researchers argued that the fundamental cause resulting in the overestimated bed expansion is that the feature of aggregative fluidization caused by particle clustering is not considered in the current several universal drag laws, such as Gidaspow, Syamlal-O'Brien drag laws, etc.…”
Section: Article In Pressmentioning
confidence: 99%
“…The Ma and Ahmadi expression for the RDF is based on the virial series for dense gases and has been widely used for CFD simulation of bubbling gas-solid fluidized beds [40][41][42][43].…”
Section: Radial Distribution Function Modelsmentioning
confidence: 99%
“…It was found that the generally poor simulation results for Geldart A particles, which could be attributed to the existence of significant cohesive inter-particle forces. Hosseini et al (2009) simulated the bubbling fluidized bed of FCC particles at high superficial gas velocities and. demonstrated the sensitivity of their system to the model's parameters such as drag function, restitution coefficient, and maximum solid packing limits.…”
Section: Introductionmentioning
confidence: 99%